Pengembangan E- Modul Berbasis Contextual Teaching and Learning (CTL) pada Materi Keberagaman Budaya Masyarakat untuk Meningkatkan Hasil Belajar di Kelas V Sekolah Dasar - Leni Susianti; Puspa Djuwita; Osa Juarsa (Jurnal Kajian Pendidikan Dasar (Kapedas), 2023)
This study aims to determine the steps for compiling e-modules, the feasibility of materials, language, design, and product effectiveness resulting from the development of CTL-based e-modules on the subject of cultural diversity in society to improve learning outcomes for fifth grade elementary school students. This research is a Research and Development (R&D) study. The model used in development is the ADDIE model. The subjects in the study were students of SDN 38 Bengkulu City, totaling 25 students in class 5 A as the experimental class, and 22 students in class 5 B as the control class. The instruments used in this study were interview guides, questionnaires, and tests in the form of multiple choice questions through pretest and posttest. To measure effectiveness, tests were carried out twice, namely before and after learning took place in the experimental class and the control class. The data analysis technique in this study was validation analysis using Aiken's V and Interrater Reliability, as well as quantitative analysis using the t-test. From the research results it is known that the results of material, language, and design validation are very feasible and well used in learning so that students are happy and interested in learning. The results of the effectiveness of e-modules effectively affect student learning outcomes. Students who use CTL-based e-modules are higher than students who only use textbooks from schools so they are declared effective.